2003
DOI: 10.1165/rcmb.4899
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Reduces Transendothelial Migration of Neutrophils and Prevents Lung Injury in Endotoxin-Induced Airway Inflammation

Abstract: We investigated the pharmacologic effects of the antioxidant Vitamin E (alpha-tocopherol [alpha-toc]) in airway inflammation induced by inhaled endotoxin. A preparation of alpha-toc incorporated in liposomes was administered intraperitoneally in mice 1 h after exposure of aerosolized endotoxin. Injection of 50 mg alpha-toc/kg significantly decreased the number of neutrophils in airspaces and prevented lung injury, monitored both as decreased lactate dehydrogenase activity in airways and reduced lung edema when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 30 publications
4
76
1
Order By: Relevance
“…Current interest in oxidative stress and antioxidants arise from the putative role of ROS in many diverse conditions such as ageing, atherosclerosis, cancer, inflammatory bowel diseases and intestinal reperfusion injury, neurodegenerative disorders, chronic renal failure, viral infections, and the immune response (Jacques et al, 1988;Harats et al, 1990;Harris et al, 1992;Powell et al, 1994;Haklar et al, 1995;Schwartz et al, 1996;Kohen et al, 1997;Stone, 1997). As we stated earlier, high doses of a-tocopherol showed benefit in animal models of respiratory distress syndrome and endotoxin-induced air way inflammation (Demling et al, 1995;Suntres et al, 1996;Fan et al, 2000;Rocksen et al, 2003). In a randomized double-blind placebo-controlled study, natural antioxidants including vitamins E and C improved lung function and reduced airway inflammation in heaves-affected horses (Kirschvink et al, 2002).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Current interest in oxidative stress and antioxidants arise from the putative role of ROS in many diverse conditions such as ageing, atherosclerosis, cancer, inflammatory bowel diseases and intestinal reperfusion injury, neurodegenerative disorders, chronic renal failure, viral infections, and the immune response (Jacques et al, 1988;Harats et al, 1990;Harris et al, 1992;Powell et al, 1994;Haklar et al, 1995;Schwartz et al, 1996;Kohen et al, 1997;Stone, 1997). As we stated earlier, high doses of a-tocopherol showed benefit in animal models of respiratory distress syndrome and endotoxin-induced air way inflammation (Demling et al, 1995;Suntres et al, 1996;Fan et al, 2000;Rocksen et al, 2003). In a randomized double-blind placebo-controlled study, natural antioxidants including vitamins E and C improved lung function and reduced airway inflammation in heaves-affected horses (Kirschvink et al, 2002).…”
Section: Discussionmentioning
confidence: 85%
“…It has cytoprotective properties that are mediated by their ability to scavange ROS and thus prevent lipid peroxidation of cell membranes (Chow et al, 1991;Traber et al, 1995). Treatment with high doses of a-tocopherol has shown benefit in animal models of acute respiratory distress syndrome (Demling et al, 1995;Suntres et al, 1996;Fan et al, 2000;Rocksen et al, 2003). In an animal model, a-tocopherol was shown to prevent lung injury in endotoxin-induced airway inflammation (Rocksen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacologic interventions and biologic response modifiers have recently been focused on pulmonary radiation protection. Intravenous or systemic delivery of compounds such as WR2721 (Amifostine), [9][10][11][26][27][28][29]32 colony stimulating factors, 31 or other antioxidant molecules 30,33,34 has the potential problem of distribution to tumor vasculature within the target volume. 27,29 Simultaneous tumor and normal tissue radiation protection would not alter the therapeutic ratio or shift to a desirable effect of normal tissue radiation protection.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on cows in the perinatal period, Pinotti et al (14) observed a slight increase in chemotactic activity following administration of α-tocopherol, which, according to the authors, may be the effect of systemic immunomobilisation in the cows during this period. Another study (16) confirmed that antioxidants may inhibit the inflammatory response within pulmonary tissue, resulting in reduced chemotaxis and phagocytosis of neutrophils isolated from mice.…”
Section: Discussionmentioning
confidence: 85%